Burden of low birth weight and short gestation from 1990–2021 and projection to 2050: assessment against 2030 malnutrition reduction targets - Jiang, Bengui; Lin, Kelly; Buys, Nicholas; Qi, Yanfei; Sun, Jing (Frontiers in Pediatrics, 2025)
BackgroundLow birth weight (LBW) and short gestation (LBWSG) are defined as birth at a gestational age <38 weeks and at a lower birth weight than the lowest risk weight of 3,500 g. Prematurity and LBW are the leading causes of global under-5 mortalities. This study aims to provide a systematic analysis of the changes in morality and disease burden of LBW and short gestation in the past 30 years to help inform health policy formation and guide resource allocation.MethodsThis study utilized data from the 2021 Global Burden of Disease Study. We measured LBWSG mortality, DALYs, and YLDs in children under 20 years of age. Data from children under 20 years of age were accessed. To assess the progress in achieving the 2030 Sustainable Development Goals of a 30% reduction in LBWSG, average annual percentage change (AAPC) was calculated on a global, regional, and national level. A mixed-effects model with sodiodemographic index (SDI) and time as the main covariates was further used to forecast LBWSG mortality and DALYs from 2022 to 2050. Countries were further classified based on their SDI scores to compare AAPC and forecasted LBWSG mortality and disease burden results.ResultsCountries with high-middle SDI scores showed the most significant reduction in LBWSG under-5 mortalities (AAPC = −0.84, 95% CI = −0.86 to −0.82), followed by countries with middle, high, and low-middle SDI. However, no significant improvements were identified in low SDI countries. Furthermore, the LBWSG burden worsened among 73 countries of all SDI and income levels. Forecasting results indicated an increase in LBWSG DALYs rate in children aged 5–19 years of age across low, low-middle, and high SDI countries.ConclusionThere are significant inequalities in the accessibility and quality of maternal and child healthcare between countries with high and low SDI scores. Temporal trends and forecasting results indicated increased disease burden for LBW and short gestation suggesting that 73 countries will not be able to achieve the 2030 nutritional target of a 30% reduction in preterm birth. Comprehensive policies to address maternal risk factors are required to reduce preterm birth, while upscaling of cost-effective life-saving interventions is needed to reduce the death of preterm infants.